Origin and evolution processes of hybrid event beds in the Lower Cretaceous of the Lingshan Island, Eastern China. Issue 4 (19th May 2018) - Yang, T.; Cao, Y.; Friis, H.; Liu, K.; Wang, Y.
ABSTRACT: On the basis of detailed sedimentological investigation, three types of hybrid event beds (HEBs) together with debrites and turbidites were distinguished in the Lower Cretaceous sedimentary sequence on the Lingshan Island in the Yellow Sea, China. HEB 1, with a total thickness of 63–80 cm and internal bipartite structures, is characterised by a basal massive sandstone sharply overlain by a muddy sandstone interval. It is interpreted to have been formed by particle rearrangement at the base of cohesive debris flows. HEB 2, with a total thickness of 10–71 cm and an internal tripartite structure, is characterised by a normal grading sandstone base, followed by muddy siltstone middle unit and capped with siltstones; the top unit of HEB 2 may in places be partly or completely eroded. The boundary between the lowest unit and the middle unit is gradual, whereas that between the middle unit and the top unit is sharp. HEB 2 may be developed by up-dip muddy substrate erosion. HEB 3, with a total thickness up to 10 cm and an internal bipartite structure, is characterised by a basal massive sandstone sharply overlain by a muddy siltstone interval. The upper unit was probably deposited by cohesive debris flow with some plant fragments and rare mud clasts. HEB 3 may be formed by the deceleration of low-density turbidity currents. The distribution of HEBs together with debrites and turbidites implies a continuous evolution process of sediment gravity flows: debris flow → hybrid flow caused by particle rearrangement → high-density turbidity current → hybrid flow caused by muddy substrate erosion → low-density turbidity current → hybrid flow caused by deceleration.